Liberation Technology: Mobile Phones and Political Mobilization in Africa - Marco Manacorda; Andrea Tesei (Center for Economic Studies and ifo Institute (CESifo), 2016)
Can digital information and communication technology (ICT) foster mass political mobilization? We use a novel geo-referenced dataset for the entire African continent between 1998 and 2012 on the coverage of mobile phone signal together with georeferenced data from multiple sources on the occurrence of protests and on individual participation in protests to bring this argument to empirical scrutiny. We find that mobile phones are instrumental to mass mobilization during economic downturns, when reasons for grievance emerge and the cost of participation falls. Estimated effects are if anything larger once we use an instrumental variable approach that relies on differential trends in coverage across areas with different incidence of lightning strikes. The results are in line with insights from a network model with imperfect information and strategic complementarities in protest provision. Mobile phones make individuals more responsive to both changes in economic conditions - a mechanism that we ascribe to enhanced information - and to their neighbors' participation – a mechanism that we ascribe to enhanced coordination. Empirically both effects are at play, highlighting the channels through which digital ICT can alleviate the collective action problem.
Keywords: D70; O55; L96; 330; mobile phones; collective action; Africa; geo-referenced data